Determinant Factors to become a Customer of Sharia Multifinance Companies among Indonesian Muslims - Rini Fatma Kartika; Ali Idrus; Ade Suherlan (Falah: Jurnal Ekonomi Syariah, 2024)
Sharia multifinance companies are one of Indonesia's Islamic non-bank financial industries that also utilize technological advances to facilitate people who want to apply for Islamic financing online. This study aims to analyse to analyze the determinants of awareness and intention of Indonesian muslim to become a customer of sharia multifinance companies. This study was quantitative by using questionnaire as the method of collecting data which distributed to a total of 418 respondents. The data analysed by using structural equation models with Smart PLS software. The results of this study found that religious commitment, awareness and reputation have a positive and significant impact on the intention to become a customer of sharia multifinance companies. The results of this study contribute to increase the understanding of sharia multifinance companies on the awareness and intention of Muslim in Indonesia to become their customer.